Few-Femtosecond Dynamics of Free-Free Opacity in Optically Heated Metals - A. Niedermayr; M. Volkov; S. A. Sato; N. Hartmann; Z. Schumacher; S. Neb; A. Rubio; L. Gallmann; U. Keller (Physical Review X, 2022)
Interaction of light with an excited free-electron gas is a fundamental process spanning a large variety of fields in physics. The advent of femtosecond laser pulses and extreme-ultraviolet sources allowed one to put theoretical models to the test. Recent experimental and theoretical investigations of nonequilibrium aluminum, which is considered to be a good real-world representation of an ideal free-electron metal, showed that, despite significant progress, the transient hot-electron/cold-ion state is not well understood. In particular, the role of plasmon broadening, screening, and electron degeneracy remains unclear. Here, we experimentally investigate the free-free opacity in aluminum on the few-femtosecond timescale at laser intensities close to the damage threshold. Few-femtosecond time resolution allows us to track the purely electronic contribution to nonequilibrium absorption and unambiguously separate it from the slower lattice contribution. We support the experiments with ab initio calculations and a nearly free electron model in the Sommerfeld expansion. We find that the simplest independent-particle model with a fixed band structure is sufficient to explain the experimental findings without the need to include changes in screening or electron scattering, contrasting previous observations in 3d transition metals. We further find that electronic heating of a free-electron gas shifts the spectral weight of the absorption to higher photon energies, and we are able to distinguish the influence of the population change and the chemical potential shift based on the comparison of ab initio calculations to a simplified free-electron model. Our findings provide a benchmark for further investigations and modeling of dense nonequilibrium plasma under even more extreme conditions.